PERAN USAID DALAM MENINGKATKAN AKSES AIR BERSIH DI HAITI MELALUI PROGRAM WATSAN (WATER AND SANITATION) - Musdalifah, Gustri; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study examines the role of the United States Agency for International Development (USAID) as an international organization in addressing the water and sanitation crisis in Haiti through the WATSAN program. Haiti, one of the poorest and most disaster-prone countries in the Caribbean, suffers from multidimensional challenges, including weak infrastructure, political instability, and limited access to clean water. These structural conditions prompted USAID to intervene with a development program focused on improving water governance, infrastructure, and community behavior. Using Clive Archer's theory of international organizations, this research analyzes USAID's function as an instrument of U.S. foreign policy, a forum for collaboration with local institutions, and an independent actor in operational development. The study employs a qualitative-descriptive approach through document analysis, including evaluation reports and government data. Findings show that USAID played a multifaceted role in the WATSAN program: building fecal sludge management facilities, supporting digital monitoring systems, and strengthening the capacity of Haitian institutions such as DINEPA and OREPA. Despite these achievements, the program faced significant challenges related to land tenure, community engagement, inter-donor coordination, and political instability. Overall, the study concludes that USAID’s involvement in Haiti illustrates the complex realities of international development organizations balancing operational goals with sustainable, locally owned outcomes. Key Words : Water and Sanitation, United States Agency for International Development, Haiti, Water Access, Sanitation